2001
DOI: 10.1359/jbmr.2001.16.5.948
|View full text |Cite
|
Sign up to set email alerts
|

Functional Impact of Human Collagen α2(XI) Gene Polymorphism in Pathogenesis of Ossification of the Posterior Longitudinal Ligament of the Spine

Abstract: Ossification of the posterior longitudinal ligament (OPLL) of the spine is the leading cause of myelopathy in Japan. In earlier studies, we provided genetic linkage and allelic association evidence of distinct differences in the human collagen ␣2(XI) gene (COL11A2) that might constitute inherited predisposition to OPLL.(1) In the present study, a strong allelic association with non-OPLL (p ‫؍‬ 0.0003) was observed with an intron 6 polymorphism [intron 6 (؊4A)], in which the intron 6 (؊4A) allele is more freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 31 publications
2
55
0
Order By: Relevance
“…Retaining exon 7 together with removal of exon 6 observed in intron 6(-4A) in the COL11A2 gene could play a protective role in the ectopic ossification process. 70 Maeda et al 71 reported a sex-specific association of the COL11A2 haplotype with OPLL in male patients. However, a recent study by Horikoshi et al 38 could not reproduce the association between this gene and OPLL.…”
Section: Pathogenesismentioning
confidence: 99%
“…Retaining exon 7 together with removal of exon 6 observed in intron 6(-4A) in the COL11A2 gene could play a protective role in the ectopic ossification process. 70 Maeda et al 71 reported a sex-specific association of the COL11A2 haplotype with OPLL in male patients. However, a recent study by Horikoshi et al 38 could not reproduce the association between this gene and OPLL.…”
Section: Pathogenesismentioning
confidence: 99%
“…Because genetic factors appear to play crucial roles in the etiology of OPLL, genetic screenings to identify susceptibility are important. To date, we have performed genetic linkage and linkage disequilibrium studies to identify the causalities of OPLL and have successfully identified collagen 11A2 (COL11A2) and collagen 6A1 (3)(4)(5)(6). We also demonstrated that an intron 6 (Ϫ4a) polymorphism of COL11A2 affects the splicing of exon 6 in ligament cells from OPLL patients (5).…”
mentioning
confidence: 99%
“…To date, we have performed genetic linkage and linkage disequilibrium studies to identify the causalities of OPLL and have successfully identified collagen 11A2 (COL11A2) and collagen 6A1 (3)(4)(5)(6). We also demonstrated that an intron 6 (Ϫ4a) polymorphism of COL11A2 affects the splicing of exon 6 in ligament cells from OPLL patients (5). Although the identification of genetic factors of OPLL has important implications, the overall picture of the molecular pathogenesis is still unclear, mainly because a subtle biological effect of the variant is the only observation, and, therefore, the biological significance of the variant is still obscure.…”
mentioning
confidence: 99%
“…This pattern was similar to that found by Lee et al 15 Polymorphisms in COL11A2 have been implicated in susceptibility to skeletal and cartilage disorders, and hearing loss. [27][28][29][30][31][32] HLA-DPB1 is an attractive candidate gene for RA within this region, as it has an important role in the immune system by presenting peptides to CD4 þ T cells. Furthermore, the other two genes encoding classical HLA class II molecules, HLA-DRB1 and HLA-DQA1, are established RA risk genes.…”
Section: Discussionmentioning
confidence: 99%